Sustainable Preparation Behavior for Kitchen Staff in Order to Limit Food Waste - Min-Yen Lu; Wen-Hwa Ko (Foods, 2023)
The concepts of culinary sustainability and avoiding the waste of surplus food have become important sustainability trends today. How the handling of surplus food can be integrated into the catering industry is a topic of concern in the industry. Kitchen staff are the vital soul of any restaurant, and we intend to discuss how kitchen staff actually behave and explore factors that influence their behaviors in order to develop an implementation model for food waste prevention. Therefore, this study explored a model of ethical sustainability, professional competence, self-efficacy, sustainable food preparation objectives, and sustainable food promotion and behavior focused on limiting food waste, using structural equation modeling (SEM) to understand the relationship between various constructs. This study used a questionnaire and surveyed employees who had been employed for more than 6 months in Taiwan. From May to August 2022, 500 questionnaires were distributed; 415 valid questionnaires were retrieved, yielding a 90.2% recovery rate. According to the structural equation modeling analysis between the dimensions, ethical sustainability should have a positive influence on professional competence in food waste prevention and self-efficacy. Professional competence in food waste prevention affected self-efficacy and behavioral intentions during food preparation; self-efficacy also significantly affected behavioral intentions towards sustainable food preparation. Similarly, behavioral intention had a positive influence on promoting sustainable behaviors. There is a significant relationship between all constructs in this study. Professional competence in food waste prevention was found to be the mediating factor between ethical sustainability and behavioral intentions toward sustainable food preparation, and self-efficacy was the mediating factor between professional competence in food waste prevention and behavioral intentions toward sustainable food preparation.